A Aktivitas Antioksidan Dari Infusa Kelakai (Stenochlaena palustris (Burm.F) Bedd) - Ali Rakhman Hakim; Amanda Shelvia Savitri; Rina Saputri (LPPM Universitas Sari Mulia, 2021)
Background: Kelakai (Stenochlaena palustris (Burn. F) Bedd.) Is a plant originating from Kalimantan that grows on peat soil. Objective: to determine the antioxidant activity of the leaves of kelakai (Stenochlaena palustris (Burm. F) Bedd.) made by infusion. Method: This type of research is true experimental and research method with post test only control group design. Kelakai made an infusion and then tested for antioxidant activity using the DPPH method. Results: The kelakai infusion positive contains flavonoids. Kelakai infusion has a very strong antioxidant activity at a concentration of 20 ppm with an absorbance value of 0.072 and an antioxidant activity of 86.90%. Kelakai infusion has an IC50 value of 6.4035 ppm. Conclusion: kelakai infusion positive contains flavonoid compounds and has a very strong antioxidant ability with an IC50 value of 6.4035 ppm. Keywords: antioxidants, flavonoids, infusion, kelakai